Effects of atmospheric-plasma system on energy efficiency improvement and emissions reduction from a diesel engine. (15th March 2019) - Chang, Ken-Lin; Amesho, Kassian T.T.; Lin, Yuan-Chung; Jhang, Syu-Ruei; Chou, Feng-Chih; Chen, Hua-Chun
Abstract: Efficient energy usage and energy saving is one of the nowadays necessity for all scientists of IC engine. This is because of the current environmental challenges that have tremendously increased concerning air pollution, particularly pollutant emissions from vehicles. Yet, industries and governments alike have disregarded this phenomenon which has been considerably contributing to climate change. It is against this background that, the research works carried out in this present study is predominantly focusing on improving energy efficiency and reducing emission levels from diesel engines. This can be achieved with the help of atmospheric-plasma system which can offer a noble solution to the above-mentioned challenges due to its potential to improve combustion efficiency which leads to energy efficiency, while reducing emission levels from diesel engines. In this study, the performance and emissions of a diesel generator supplemented with an atmospheric-plasma system was examined. The diesel engine was used to examine the effects of fuel composition, or brake specific fuel consumption, thermal efficiency and pollutant emissions at different plasma system voltages. To this end, we equally examined the effects of atmospheric-plasma system on energy efficiency improvement and emissions reduction from diesel engine as the main purpose of this study. We do so by testing the diesel-fueled engine generator under the atmospheric-plasma system. The tests were carried out at a constant state condition with the engine running at 2200 rpm with torque and power outputs of 10.4 Nm (75% of the max load) and 2.1 kW, separately, for the tested fuels and this was used to increase the output voltage of the plasma system during this study. The plasma system ionized the intake air and improved the formation of free radicals upon combustion. During this study, the output voltage of the plasma was set within the range of 0–7 kV. The experimental results have indicated that formaldehyde, acetaldehyde and acrolein account for more than 75% of total carbonyl compounds emissions. Simultaneously, it was also observed from the results that higher plasma system voltage reduces pollutants emissions levels. Hence, such reduction is predominantly evident for nitrogen oxides, particulate matters and carbon monoxide. However, the marginal improvements of engine performance and emissions reduction become insignificant when the plasma system voltage reaches 6 kV. On the other hand, increasing the amount of plasma system voltages in diesel engine continues to significantly reduce pollutant emissions. Graphical abstract: Image 1 Highlights: Atmospheric plasma system saves energy and reducing emission levels. Formaldehyde, acetaldehyde and acrolein accounts for 75% of carbonyl compounds. Higher plasma system voltage lowers pollutants emissions levels. Improve engine performance as plasma system voltage reaches 6 kV. PM concentration has been reduced considerably by higher plasma voltage.